Understanding Interest Rate Volatility - Desi Volker (Copenhagen Business School (CBS), 2016)
This thesis is the result of my Ph.D. studies at the Department of Finance of the Copenhagen Business School. It consists of three essays covering topics related to the term structure of interest rates, monetary policy and interest rate volatility. The rst essay, Policy Uncertainty and Interest Rates", examines the role of monetary policy uncertainty on the term structure of interest rates. The second essay, Regime-Switching A ne Term Structure Model with Stochastic Volatility" (co-authored with Sebastian Fux), investigates the ability of the class of regime switching models with and without stochastic volatility to capture the main stylized features of U.S. interest rates. The third essay, Risk Premia in the Interest Rate Swap Market", investigates the time-series and cross-sectional properties of the compensation demanded for holding interest rate variance risk. The essays are self-contained and can be read independently. There is however a common thread in the themes covered as all essays focus on the understanding of interest rate volatility, its time-variation and main determinants.
hdl:10398/9340
Keywords: 650